Estimation of short-term C-fixation in a New England temperate tidal freshwater wetland - Gailynn Milligan; Helen M. Poulos; Martha S. Gilmore; Graeme P. Berlyn; Joseph Milligan; Barry Chernoff (Heliyon, 2019)
Wetlands provide myriad ecosystem services, yet the C-cycling of vegetation within interior freshwater tidal wetlands remains poorly understood. To this end, we estimated species’-specific plant carbon-fixation rates for the six dominant wetland plant species in a large temperate freshwater wetland in Connecticut, USA. We integrated field C-fixation rates for dominant marsh plant species with satellite-derived leaf area index and wetland aerial extent data to: 1) quantify seasonal and species-level differences in wetland plant C-fixation rates; and 2) estimate whole-marsh emergent aquatic plant C-fixation rates over the growing season. Photosynthetic rates differed significantly by species and month (P < 0.05). Acorus calamus had the highest photosynthetic rate between May and September, and Acer saccharinum had the lowest. By integrating field photosynthetic data with wetland aerial extents, we estimated that the total annual C uptake by the vegetation in this wetland, which was 2868 Mg C. Herbaceous vegetation contributed to most of that stock (herbaceous vegetation = 2099.2 Mg C, forest = 769.6 Mg C), although soil respiration likely offset those numbers substantially. Our results demonstrate the importance of short-term above-ground freshwater wetland C-fixation, and that the emergent vegetative component of these wetland systems are key components of the tidal freshwater wetland C cycle.